2022
DOI: 10.1021/acsami.2c09477
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Interfacial Diffusion in Mg3Sb2 Thermoelectric Materials through an Mg4.3Sb3Ni/Mg3.2Sb2Y0.05/Mg4.3Sb3Ni-Graded Structure

Abstract: The Zintl compound, n-type Mg3Sb2, has been extensively investigated as a promising thermoelectric material. However, performance degradation caused by the loss of Mg element during device preparation and service is a main disadvantage in its utilization in thermoelectric devices. To suppress volatilization, diffusion, or reaction of Mg, we designed a graded concentration junction to control the interfacial elemental diffusion and improve the stability of the thermoelectric joint. We utilized the reaction prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…The raw testing data can be seen in Figure S4, Tables S1, S2, and S3, Supporting Information. In contrast, the k ρc and k σs in the reported literature [36,38,40] are over 37 µΩ cm 2 s 1/2 and 24 MPa s 1/2 , respectively, which are higher than our as-fabricated TEiM/TEcM interfaces, suggesting that the operating lifespan of FeCrTiMnMg/Mg 3 Sb 1.5 Bi 0.5 interfaces is significantly increased, which should be the most stable electrode contact interface in the reported Mg 3 Sb 2 -based TE devices.…”
Section: Increase In the Stability Of Teim/tecm Interfaces Using Fecr...mentioning
confidence: 95%
See 1 more Smart Citation
“…The raw testing data can be seen in Figure S4, Tables S1, S2, and S3, Supporting Information. In contrast, the k ρc and k σs in the reported literature [36,38,40] are over 37 µΩ cm 2 s 1/2 and 24 MPa s 1/2 , respectively, which are higher than our as-fabricated TEiM/TEcM interfaces, suggesting that the operating lifespan of FeCrTiMnMg/Mg 3 Sb 1.5 Bi 0.5 interfaces is significantly increased, which should be the most stable electrode contact interface in the reported Mg 3 Sb 2 -based TE devices.…”
Section: Increase In the Stability Of Teim/tecm Interfaces Using Fecr...mentioning
confidence: 95%
“…Thus, it is difficult to balance the high σ s and low ρ c values of a single‐element TEiM. Some alloying TEiM layers for n‐type Mg 3 Sb 1‐ x Bi x TEcM legs, including 304 stainless steel (304SS), [ 36 ] Mg 2 Cu, [ 10 ] Fe 90 Sb 10 , [ 37 ] and Mg 3.4 Sb 3 Ni [ 38 ] were subsequently reported to show lower ρ c values. Very recently, Song et al reported that the NiFe/Mg 3 Bi 1.5 Sb 0.5 contact exhibits a highly stable ρ c of 13 µΩ cm 2 after aging for over 2100 h. [ 39 ] The authors have suggested an alloying approach to design the TEiM rather than using available alloys, which has already been verified as an effective technique route with some necessary characteristics, including high bonding propensity, coefficient of thermal expansion (CTE) matching, diffusion passivation, and dopant inactivation.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8] Ideal thermoelectric materials not only should possess high thermoelectric performance, but also meet the requirements of non-toxic, good chemical stability, and thermal stability in practical applications. [9][10][11][12][13][14][15] Nowadays, many tellurides have been developed as state-of-the-art thermoelectric materials, such as Bi 2 Te 3 , PbTe, SnTe and GeTe-AgSbTe 2 . [16][17][18][19][20][21] However, these materials contain the common toxic and scarce tellurium, which serves as the main constraint for their large-scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, Mg 3 Sb 2 -based compounds have attracted the interest of many researchers due to their abundant and nontoxic constituent elements, cost-effectiveness and advanced thermoelectric properties. [9,12,14,22,23] In particular, Mg 3 Sb 2 has high Seebeck coefficient and low lattice thermal conductivity which is 0.7 ~0.9 Wm À 1 K À 1 at RT. [24] Unfortunately, this compound has a low electrical conductivity, [25] which originates from its low carrier concentration and carrier mobility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation